Advances in seaweed cultivation and utilisation in Asia : proceedings of a workshop held in conjunction with the 7th Asian Fisheries Forum, Penang, Malaysia, December 2004 - Asian Fisheries Forum (7th : 2004 : George Town, Pinang); Phang, Siew Moi; Critchley, Alan T.; Ang, Put O.; University of Malaya. Martime Research Centre (Kuala Lumpur : University of Malaya Maritime Research Centre, 2006)
Includes bibliographical references